If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(w + -6) = 3w + 9 Reorder the terms: -6(-6 + w) = 3w + 9 (-6 * -6 + w * -6) = 3w + 9 (36 + -6w) = 3w + 9 Reorder the terms: 36 + -6w = 9 + 3w Solving 36 + -6w = 9 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 36 + -6w + -3w = 9 + 3w + -3w Combine like terms: -6w + -3w = -9w 36 + -9w = 9 + 3w + -3w Combine like terms: 3w + -3w = 0 36 + -9w = 9 + 0 36 + -9w = 9 Add '-36' to each side of the equation. 36 + -36 + -9w = 9 + -36 Combine like terms: 36 + -36 = 0 0 + -9w = 9 + -36 -9w = 9 + -36 Combine like terms: 9 + -36 = -27 -9w = -27 Divide each side by '-9'. w = 3 Simplifying w = 3
| -2(2x+3)+8x=6(x-1)+3x | | 8-6x=3-7x | | 10=2h | | 28.50+8.75w=104.75+6.50w | | 9Y-81x=108 | | 6q+3q-q=24findq | | 90x+x=90 | | 8x+4y=10y | | 6x-2=-4c+8x | | 180x+x=180 | | 2(2-x)=8-2(2-x) | | f(x)=(15x) | | y+16=20 | | 90x+x=180 | | 10-.25x=.5+4 | | 4(v+5)+8v=32 | | x^2-10x-27=0 | | x-76y=0 | | 12x^2+6x+82=0 | | 4x^2-5sinx=0 | | -5n-3n+2=34 | | 18x-6=-10 | | 4x^2-5sinx= | | (6+u)(3u+4)=0 | | (27x)27=21(21+2x+8) | | 2(2-x)=8-2(-x) | | ln(6)+ln(x)=4 | | 2x+3(2+5)=X | | 4(3x^2+2x)-12x^2=2(8x+6) | | 4x+3(x-6)=-11 | | -6-(21-6X)=-51+2X | | 4x-9y+6x+3y-2x=0 |